Determination of FICI Value of Combination of Ethanol Extract of Aloe Vera (L.) Burm. f. Leaf Peel and Chloramphenicol Against Bacterial Pathogens - Sari, Rafika (Brawijaya University, 2023)
ABSTRACT The Increasing case of antibiotic resistance encourages a new action that is the combination plant extracts and antibiotics. Aloe vera leaf skin (Aloe vera (L.) Burm f.) contains phenols, flavonoids and anthraquinones that act as antimicrobials. The aim of research is to determine the value of FICI (Fractional Inhibitory Concentration Index) combination of ethanol extract of Aloe vera leaf skin (Aloe vera (L.) Burm f.) and chloramphenicol against pathogenic bacteria. The determination of MIC (Minimum Inhibitory Concentration) value of ethanol extract for Aloe vera leaf skin (Aloe vera (L.) Burm. F.) and chloramphenicol use disc-paper diffusion method. The combination solution is created by a ratio of 1: 1 volumes from the every MIC values. The determination of FICI values ​​was analyzed by descriptive. The combination of Aloe vera leaf skin extract (Aloe vera (L.) Burm. F.) and chloramphenicol are used for Salmonella typhi bacteria which are 12.5mg / ml and 8 μg / ml, and for Bacillus subtilis bacteria is 2.5 mg / ml and 4 μg / ml resulted in inhibit zone 7.77 ± 0.25 and 7.83 ± 0.36. The combination of FICI value is 2 and it has indifference characteristics (not different) when the researcherd compared between single extract and single chloramphenicol. Aloe vera leaf skin ethanol extract (Aloe vera (L.) Burm. f.) and chloramphenicol may inhibit the growth of Salmonella typhi and Bacillus subtilis bacteria and both of the combinations show indifference characteristics of FICI 2 values. Keywords: FICI, Aloe Vera, Antibacterial, Chloramphenicol